2016
DOI: 10.1038/cddis.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

ATP2C1 gene mutations in Hailey–Hailey disease and possible roles of SPCA1 isoforms in membrane trafficking

Abstract: ATP2C1 gene codes for the secretory pathway Ca2+/Mn2+-ATPase pump type 1 (SPCA1) localizing at the golgi apparatus. Mutations on the human ATP2C1 gene, causing decreased levels of the SPCA1 expression, have been identified as the cause of the Hailey–Hailey disease, a rare skin disorder. In the last few years, several mutations have been described, and here we summarize how they are distributed along the gene and how missense mutations affect protein expression. SPCA1 is expressed in four different isoforms thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 123 publications
4
61
0
Order By: Relevance
“…Up to now, including the mutations we identified in this study, a total of 209 mutations in ATP2C1 have been found. However, all of them followed a uniform distribution without hotspots or clusters, which is consistent with previous investigations …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Up to now, including the mutations we identified in this study, a total of 209 mutations in ATP2C1 have been found. However, all of them followed a uniform distribution without hotspots or clusters, which is consistent with previous investigations …”
Section: Discussionsupporting
confidence: 92%
“…However, all of them followed a uniform distribution without hotspots or clusters, which is consistent with previous investigations. 8 Along with our findings, 6.2% (13/209) of mutations were in the N-terminus/S1 domain. The N-terminus contained a Ca 2+binding EF hand-like motif which seemed to regulate ion affinity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…SPCA1 consists of actuator, nucleotide-binding, phosphorylation domains, and 10 transmembrane helices. 1 The patient's mutation resides in second transmembrane domain whose interaction with actuator/phosphorylation domains is critical for Ca 2+ release into Golgi, 2 and might be compromised by this mutation.…”
Section: E482mentioning
confidence: 99%